Isolation of endophytic bacteria and evaluation of fermented avicennia marina fruit filtrate as natural antimicrobials against staphylococcus aureus - Galih Dwiki Ramanda; Anggraini Putri Utami; Yuyun Nisaul Khairillah; Nur Jati Jagad; M. Fiqri Baihaqi; Annisa Nasyawa Fahira (Arfak Chem: Chemistry Education Journal, 2026)
Antimicrobial resistance (AMR) has become a major global health challenge, necessitating the exploration of alternative antimicrobial sources from natural products. This study aimed to determine the optimum fermentation time, characterize the colony morphology and Gram-staining characteristics of endophytic bacterial isolates, and evaluate their antimicrobial activity against Staphylococcus aureus. This study employed a quantitative laboratory experimental approach. Endophytic bacteria were isolated from Avicennia marina fruit through serial dilution and characterized based on colony morphology and Gram-staining characteristics. Antimicrobial activity was evaluated using the disk diffusion method. Five endophytic bacterial isolates (AM41–AM45) were successfully obtained, consisting of three Gram-positive and two Gram-negative isolates. Among them, isolate AM41 exhibited the highest inhibitory activity against S. aureus (19.71 mm), followed by AM45 (8.83 mm) and AM42 (8.00 mm), whereas the remaining isolates showed no inhibitory activity. Differences in antimicrobial activity were observed among the fermentation times tested. The largest inhibition zone was recorded after 72 h of fermentation (21.67 mm), followed by 96 h (20.07 mm), while shorter fermentation periods produced lower inhibitory activity. These findings indicate that endophytic bacterial isolates and fermented filtrates of A. marina fruit possess antimicrobial potential against S. aureus. Under the conditions tested, the highest antimicrobial activity of the fermented filtrate was observed after 72 h of fermentation